Phytochemical analysis in conjunction with in vitro a-glucosidase inhibitory and antioxidant activities of three Diospyros species from East Kalimantan, Indonesia - RICO RAMADHAN; NISA’UR ROSYIDAH; YAZDANIYAR FAJRI HALIMI FIRDAUS; IRMAYANTI TRI KURNIA; DINDA AYU LESTARI; KIETTIPUM PHONTREE; PREECHA PHUWAPRAISIRISAN; LUKMAN RIYADI; ARRIZAL RAHMAN; NURLITA ABDULGANI; SILVI ARUM MARETNA; KAYLA NAULIA FADHILA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ramadhan R, Rosyidah N, Firdaus YFH, Kurnia IT, Lestari DA, Phontree K, Phuwapraisirisan P, Riyadi L, Rahman A, Abdulgani N, Maretna SA, Fadhila KN. 2023. Phytochemical analysis in conjunction with in vitro a-glucosidase inhibitory and antioxidant activities of three Diospyros species from East Kalimantan, Indonesia. Biodiversitas 24: 4783-4790. Locals who live in forested areas have long relied on Non-Timber Forest Products (NTFPs) for their traditional ceremonies, food, and medicine. As non-timber forest products, medicinal plants are of interest since they are used by locals in East Kalimantan regions, Indonesia, for local traditional medicine. In the search for new potential antidiabetics and antioxidants created from natural resources, the authors concentrated on medicinal plants traditionally used in East Kalimantan and ethnopharmacological data. The purpose of this study is to evaluate the dual roles of non-timber forest products, such as three Diospyros L. species, in a-glucosidase inhibition, antioxidant (free radical scavenging activity against DPPH and ABTS), and CUPRAC in-vitro activities. This study showed that the strongest a-glucosidase inhibitory activity was found in ethyl acetate and ethanol residue extracts of Diospyros celebica Bakh., with IC50 values of 4.5804±0.14 ug/mL and 3.8236±0.19 ug/mL respectively, which were more potent than quercetin as a positive standard. Additionally, the antioxidant test revealed that leaf extracts of three Diospyros species from East Kalimantan are excellent sources of natural antioxidants, as demonstrated by the SC50 values. The findings of this study support and validate the use of leaf extracts of three Diospyros species in traditional East Kalimantan medicine.